Perceptual-cognitive performance of youth soccer players in a 360°-environment – An investigation of the relationship with soccer-specific performance and the effects of systematic training. (July 2022) - Ehmann, Paul; Beavan, Adam; Spielmann, Jan; Mayer, Jan; Ruf, Ludwig; Altmann, Stefan; Forcher, Leon; Klever, Niklas; Rohrmann, Sonja; Nuß, Christian; Englert, Chris
Abstract: Introduction: Soccer is a complex game in which athletes perform in a dynamic 360°-environment. The results of numerous studies highlight the importance of perceptual-cognitive functions for soccer performance. Moreover, in recent years, the idea of improving sports performance through systematic perceptual-cognitive training has been increasingly investigated. Contradictory results and limitations in previous research call for further investigation. The current study aims to investigate both the relationship between perceptual-cognitive performance in a dynamic 360°-environment and soccer performance as well as the effects of perceptual-cognitive training in such an environment on soccer performance. Methods: 42 youth soccer players aged 11–13 years were tested at a first time of measurement (T1) on their perceptual-cognitive functions using a 360°-multiple object tracking task (360-MOT) and a visuospatial attention task. Soccer performance was assessed using an isolated, validated 360°-passing task and a small-sided game. Subsequently, participants were randomly divided into a perceptual-cognitive training group, an active control group, or a passive control group. Participants in the training group received 360-MOT training twice per week during a 5-week intervention phase, while participants in the active control group received a pseudo video training. Perceptual-cognitive and soccer-specific performance was assessed after the intervention phase at a second time of measurement (T2). Results: At T1, there was a significant positive relationship between 360-MOT performance and both the accuracy score in the 360°-passing task and the defensive performance score in the small-sided game. Regarding the perceptual-cognitive training intervention, the analysis at T2 revealed significant task-specific training effects but no transfer effects on perceptual-cognitive or soccer-specific performance. Conclusions: The results highlight the relevance of perceptual-cognitive performance in a 360°-environment for soccer-specific performance but question the effects of short isolated perceptual-cognitive training interventions on soccer-specific performance. Highlights: Cognitive functions of youth soccer players assessed and trained in 360°-space. Positive relationship between cognitive performance and soccer performance. 360°-multiple object tracking training leads to task-specific training effects. No transfer effects of cognitive training on soccer performance observed.